Divergências entre o parecer prévio do Tribunal de Contas do Estado (TCE) e o resultado do julgamento das contas anuais de prefeitos em Pernambuco - Lins, Cristiana de Meira (2012)
The current study has the objective of identify what are the basis that lead some of the City Councils of Pernambuco not to follow the prior opinion of the State Audit Office on the matter of the judgment of the mayors’ annual bills. Considering that a significant number of trials executed by the City Councils concerning Mayors annual bills do not follow the recommendations stated by the priors notions from the State Audit Office, initially there have been identified theoretical approaches regarding the structure of the relation between the Executive and the Legislative Power which offer aids for the correct understanding of the politics of the City Councils on those trials. Another highlight was the technical and administrative views offered by the legislative process of the bills trails, which are susceptible to analysis and judicial reviews by the Public Ministry aiming to annulment if the trial do not demonstrate a officially registered legal motivation which serve the constitutionals arrangements. The current study was accomplished by means of bibliographic, documental and field researches, obtained through interviews with councilors of the City Councils of Pernambuco. For the data analysis it was chosen a qualitative methodology of the content analysis. The results of the current research identified that the basis which lead some of the City Councils of Pernambuco not to follow the prior opinion of the State Audit Office on the matter of the judgment of the mayors’ annual bills were not formally described in the legislative process, in which the researched official documents do not show the legal requirements of motivation, nor explain the reasons why the State Audit Office’s legal opinion was not followed. The interviewed councilors opinion lead to the understanding that such technical basis were politically based, instead of technically based, explained by the interference of the Executive Power over the Legislative.